(untitled) (International Journal of Nursing Education, 2019)
Background: Field trip for case study is an active learning approach that can be used to promote motivation, student engagement and academic achievement. However, it is not widely apply in nursing lecture class. Purpose: An active learning experience, field trip for case study, was created and implemented in the Midwifery course in order to improve teaching strategy and learning outcomes. Methodology: Action research method was employed. Participants were 160 third year nursing students enrolled in the Midwifery course. Three main active learning activities were: 1) participating in a field trip for case study, 2) learning from case study, and 3) presentation of case study. Results: The findings indicated that nursing students had positive learning experiences, achieved learning outcomes, and were satisfied with learning activities. Well-planned activities of the field trip for study, wellconstructed for active learning strategies, and additional instructional media were suggested. Conclusion: The field trip for case study could be used as an active learning strategy in nursing education